Novel microbiome signatures for non‐invasive diagnosis of adenoma recurrence after colonoscopic polypectomy - Liang, Jessie Qiaoyi; Zeng, Yao; Kwok, Grace; Cheung, Chun Pan; Suen, Bing Yee; Ching, Jessica Y. L.; To, Ka Fai; Yu, Jun; Chan, Francis K. L.; Ng, Siew Chien (Alimentary pharmacology & therapeutics, 2022)
Summary Background We previously reported a panel of novel faecal microbiome gene markers for diagnosis of colorectal adenoma and cancer. Aim To evaluate whether these markers are useful in detecting adenoma recurrence after polypectomy. Methods Subjects were enrolled in a polyp surveillance study from 2009 to 2019. Stool samples were collected before bowel preparation of index colonoscopy (baseline) and surveillance colonoscopy (follow‐up). Fusobacterium nucleatum (Fn), Lachnoclostridium marker (m3), Clostridium hathewayi (Ch) and Bacteroides clarus were quantified in baseline and follow‐up samples by quantitative polymerase chain reaction (qPCR) to correlate with adenoma recurrence. Recurrence was defined as new adenomas detected >6 months after polypectomy. Faecal immunochemical test (FIT) was performed for comparison. Results A total of 161 baseline and 104 follow‐up samples were analysed. Among patients with adenoma recurrence, Fn and m3 increased (both P < 0.05) while Ch were unchanged in follow‐up versus baseline samples. Among patients without recurrence, Fn and m3 were unchanged while Ch decreased (P < 0.05) in follow‐up versus baseline samples. Logistic regression that included changes of m3, Fn and Ch at follow‐up compared with baseline achieved an area under receiver operating characteristic curve (AUROC) of 0.95 (95%CI: 0.84‐0.99) with 90.0% sensitivity and 87.0% specificity for detecting recurrent adenoma. Combination of m3, Fn and Ch at follow‐up sample achieved AUROC of 0.74 (95%CI: 0.65‐0.82) with 81.3% sensitivity and 55.4% specificity for detecting recurrent adenoma. FIT showed limited sensitivity (8.3%) in detecting recurrent adenomas. Conclusion Our combinations of faecal microbiome gene markers can be potentially useful non‐invasive tools for detecting adenoma recurrence. Faecal microbiome gene markers can be potentially useful non‐invasive tools for detecting adenoma recurrence.